Use and outcome of minimally invasive pancreatic surgery in the European E-MIPS registry. Issue 4 (April 2023) - van der Heijde, Nicky; Vissers, Frederique L.; Manzoni, Alberto; Zimmitti, Giuseppe; Balsells, Joaquim; Berrevoet, Frederik; Bjornsson, Bergthor; van den Boezem, Peter; Boggi, Ugo; Bratlie, Svein O.; Burdio, Fernando; Coratti, Andrea; et al.
Abstract: Background: The European registry for minimally invasive pancreatic surgery (E-MIPS) collects data on laparoscopic and robotic MIPS in low- and high-volume centers across Europe. Methods: Analysis of the first year (2019) of the E-MIPS registry, including minimally invasive distal pancreatectomy (MIDP) and minimally invasive pancreatoduodenectomy (MIPD). Primary outcome was 90-day mortality. Results: Overall, 959 patients from 54 centers in 15 countries were included, 558 patients underwent MIDP and 401 patients MIPD. Median volume of MIDP was 10 (7–20) and 9 (2–20) for MIPD. Median use of MIDP was 56.0% (IQR 39.0–77.3%) and median use of MIPD 27.7% (IQR 9.7–45.3%). MIDP was mostly performed laparoscopic (401/558, 71.9%) and MIPD mostly robotic (234/401, 58.3%). MIPD was performed in 50/54 (89.3%) centers, of which 15/50 (30.0%) performed ≥20 MIPD annually. This was 30/54 (55.6%) centers and 13/30 (43%) centers for MIPD respectively. Conversion rate was 10.9% for MIDP and 8.4% for MIPD. Overall 90 day mortality was 1.1% (n = 6) for MIDP and 3.7% (n = 15) for MIPD. Conclusion: Within the E-MIPS registry, MIDP is performed in about half of all patients, mostly using laparoscopy. MIPD is performed in about a quarter of patients, slightly more often using the robotic approach. A minority of centers met the Miami guideline volume criteria for MIPD.